2022
DOI: 10.1044/2021_ajslp-21-00101
|View full text |Cite
|
Sign up to set email alerts
|

Using an Implementation Framework to Survey Outcome Measurement and Treatment Practices in Aphasia

Abstract: Purpose: Best practices in the field of aphasia rehabilitation increasingly acknowledge a whole-person approach that values interventions aimed at reducing impairments, while also recognizing the impact of aphasia on participation and quality of life. Guided by the Consolidated Framework for Implementation Research (CFIR), this study aimed to examine whether current clinical practices along levels of service provision reflect this whole-person, multifaceted approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…However, it is necessary to recognize that client and provider interactions (and thus engagement) do not exist within a vacuum but are embedded in and influenced by the broader healthcare system. Healthcare policy and incentive structures can influence clinical workflow and culture within rehabilitation settings and may not be in concordance with individual client needs and priorities (Tierney‐Hendricks et al., 2021). Therefore, there may be organizational level barriers that hinder a clinician's ability to be: a friend, invested, adaptable, a co‐creator, encouraging and dependable.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to recognize that client and provider interactions (and thus engagement) do not exist within a vacuum but are embedded in and influenced by the broader healthcare system. Healthcare policy and incentive structures can influence clinical workflow and culture within rehabilitation settings and may not be in concordance with individual client needs and priorities (Tierney‐Hendricks et al., 2021). Therefore, there may be organizational level barriers that hinder a clinician's ability to be: a friend, invested, adaptable, a co‐creator, encouraging and dependable.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in provision based on workplace setting is a key variable (Manning et al, 2020) with more intensive therapy provided in the inpatient rehabilitation setting than other settings (Verna et al, 2009) and more barriers to meeting aphasia guideline recommendations experienced by those in acute versus rehabilitation (Shrubsole et al, 2019b). A US survey of 90 SLTs found functional communication was a more common therapy target in the community setting (Tierney-Hendricks et al, 2022). Taylor et al (2015) found that institutional goals played a role in therapy intensity (e.g., there was a focus in some settings on discharge planning and reducing length of stay rather than providing intensive rehabilitation), see also Putman et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…While clinical practice guidelines emphasise the importance of measuring outcomes, there remains great variability in how this practice is operationalised in clinical settings. Addressing this variability is challenging due to limited understanding of the factors that drive clinician practice (Arnold et al, 2020;Simmons-Mackie et al, 2005;Tierney-Hendricks et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating aphasia outcome measurement practice reveal considerable variability (Arnold et al, 2020;Kiran et al, 2018;Simmons-Mackie et al, 2005;Tierney-Hendricks et al, 2022). Most recently, Tierney-Hendricks and colleagues (2022) used a crosssectional survey to explore the outcome measurement and treatment practices of speechlanguage pathologists who work with people with aphasia in the United States.…”
Section: Introductionmentioning
confidence: 99%